2012
DOI: 10.1371/journal.pntd.0001594
|View full text |Cite
|
Sign up to set email alerts
|

Taenia solium Infections in a Rural Area of Eastern Zambia-A Community Based Study

Abstract: Background Taenia solium taeniosis/cysticercosis is a parasitic infection occurring in many developing countries. Data on the status of human infections in Zambia is largely lacking. We conducted a community-based study in Eastern Zambia to determine the prevalence of human taeniosis and cysticercosis in a rural community.Methods and FindingsStool and serum samples were collected from willing participants. Geographical references of the participants' households were determined and household questionnaires admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
93
9
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 47 publications
14
93
9
1
Order By: Relevance
“…Other studies using similar antibody detecting techniques have reported prevalence of 7.4% in South Africa and 20.5% in Mozambique [6]. The prevalence in this study, however, is far lower than the 45.3% (n = 830) reported in Mbozi district of Tanzania [7] and the 40.8% reported in Burundi [17], both of which studies also used the antibody ELISA technique.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Other studies using similar antibody detecting techniques have reported prevalence of 7.4% in South Africa and 20.5% in Mozambique [6]. The prevalence in this study, however, is far lower than the 45.3% (n = 830) reported in Mbozi district of Tanzania [7] and the 40.8% reported in Burundi [17], both of which studies also used the antibody ELISA technique.…”
Section: Discussioncontrasting
confidence: 74%
“…Prevalence of human cysticercosis has been reported in South Africa (7.4%), Mozambique (20.5%), Democratic Republic of Congo (21.6%), Eastern Zambia (5.8%) [6], and Mbozi district of Tanzania (45.3%) [7] by researchers using different diagnostic methods. Though efforts in recent times have been made to document porcine cysticercosis in Nigeria [8][9][10], reliable epidemiological information on human cysticercosis is still limited, even among atrisk groups.…”
Section: Introductionmentioning
confidence: 99%
“…Niclosamide is currently used to treat tapeworm infection (15). Application of niclosamide in the treatment of cancer was first reported for colorectal cancer (16).…”
Section: Discussionmentioning
confidence: 99%
“…Niclosamide was originally developed for the treatment of tapeworm infection and is clinically used worldwide (14,15 (18) and inhibition of the canonical Wnt signaling pathway (19). Niclosamide also downregulates the expression of cyclin D1, one of the target molecules of the Wnt pathway, via glycogen synthase kinase-3β (17,20).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the prevalence of human Taenia solium cysticercosis in communities has been assessed as this requires blood analysis only. In cysticercosis endemic areas of the Democratic Republic of Congo, Burkina Faso and Zambia the prevalence of Taenia solium cysticercosis as measured with an antigen-ELISA was 22%, 10% and 5.8%, respectively [52][53][54]. Indirect approaches are used to get an impression about the prevalence of people with NCC in a certain population and often people suffering from epileptic seizures or epilepsy are included into these studies.…”
Section: Prevalence Of Neurocysticercosis In Sub-saharan Africamentioning
confidence: 99%